2019
DOI: 10.1101/759498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A compact vocabulary of paratope-epitope interactions enables predictability of antibody-antigen binding

Abstract: Antibody recognition of antigen relies on the specific interaction of amino acids at the paratopeepitope interface. A long-standing question in the fields of immunology and structural biology is whether paratope-epitope interaction is predictable. A fundamental premise for the predictability of paratope-epitope binding is the existence of structural units that are universally shared among antibody-antigen binding complexes. Here, we identified structural interaction motifs, which together compose a vocabulary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 144 publications
(176 reference statements)
3
75
0
Order By: Relevance
“…This necessitates relevant feature encoding. Indeed, studies have shown that feature engineering is essential for the prediction of paratope-epitope binding (22) and that it can also improve the performance of models for more general bioinformatics problems (23). Moreover, when complex machine learning methods are applied to small datasets, the dangers of overfitting and memorization of examples pose an even bigger threat.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates relevant feature encoding. Indeed, studies have shown that feature engineering is essential for the prediction of paratope-epitope binding (22) and that it can also improve the performance of models for more general bioinformatics problems (23). Moreover, when complex machine learning methods are applied to small datasets, the dangers of overfitting and memorization of examples pose an even bigger threat.…”
Section: Introductionmentioning
confidence: 99%
“…from sequence data alone, is much more difficult. It would involve de novo structure and binding prediction, which are not currently practical, although much recent work focuses on these problems [56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Each simulated repertoire was then randomly assigned to either the positive or negative class, with 2, 500 repertoires per class. In the repertoires assigned to the positive class, we implanted motifs with an average length of 4 AAs, following the results of the experimental analysis of antigenbinding motifs in antibodies and T-cell receptor sequences by (Akbar et al, 2019). We varied the characteristics of the implanted motifs for each of the 18 datasets with respect to the following parameters: (a) ρ, the probability of a motif being implanted in a sequence of a positive repertoire, i.e.…”
Section: A31 Simulated Immunosequencing Datamentioning
confidence: 99%